The impact of cascade screening in familial hypercholesterolemia diagnosis - Gomes, A. (2012)
Familial hypercholesterolemia (FH) is a genetic disorder of cholesterol metabolism caused by mutations in LDLR, APOB and PCSK9 genes. It’s characterized by an increase of total and LDL cholesterol levels leading to premature cardiovascular disease. According to the frequency of the disease in most European countries (1:500 individuals) it is estimated that in Portugal exists about 20.000 cases of FH, but this disease is severe under-diagnosed in our country. Cascade screening (CS) is as method for identifying individuals at risk of a genetic condition by a process of family tracing through molecular studies, allowing the rapid identification of new FH cases within a family.